Latihan ROM Pasif Unilateral dan Bilateral terhadap Peningkatan Kekuatan Otot Akibat Stroke Iskemik - Ratna Fithriyah Sholihany; Agung Waluyo; Diana Irawati (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2021)
This study aims to compare the effectiveness of unilateral ROM and bilateral ROM exercises to increase muscle strength in post-hospitalized clients with hemiparesis due to ischemic stroke. The research method used is a quasi experimental two group pre and post test design. The results showed that there was an effect of both groups on increasing muscle strength with a p-value of 0.000, in conclusion, bilateral ROM exercises had a higher impact on increasing muscle strength compared to unilateral ROM exercises. Keywords: Muscle Strength, Bilateral ROM, Unilateral ROM, Ischemic Stroke